The pastor in print genre, audience, and religious change in early modern England - Tan, Amy G. (Politics, culture, and society in early modern Britain., 2022)
'The Pastor in Print' explores the phenomenon of early modern pastors who chose to become print authors, addressing ways authorship could enhance, limit or change clerical ministry and ways pastor-authors conceived of their work in parish and print. It identifies strategies through which pastor-authors established authorial identities, targeted different sorts of audiences and strategically selected genre and content as intentional parts of their clerical vocation.